Arabic Rules Between Philosophy of Language and Grammar Criterion: A Modernist Approach - Hany Ismail Ramadan (Darulfunun Ilahiyat)
This research aims to discuss the grammar of the Arabic language from two angles: the philosophy of language as a full-fledged structure, and Arabic grammar as a description of this entity. Accordingly, the research raises the fundamental question of whether the rules of the Arabic language should be presented to non-native speakers in terms of Arabic grammar to facilitate and simplify learning, or whether starting with the language itself and its representations, formulating its rules to meet the learners’ needs is more worthwhile and compatible with modern linguistic lessons? Branching from this question are legitimate sub-questions about the renewal of Arabic grammar and its consequences, the usefulness of old Arabic grammar in language acquisition, the specificity of non-native Arabic learners and their needs. As required by the nature of the research, the article seeks to present a linguistic approach that can serve as a scientific basis for use in preparing a matrix to compose an educational curriculum for non-Arabic speakers to learn Arabic grammar.